Controllability of the pore characteristics of B4C/C preform prepared by gel-casting and the properties of RBBC composites. Issue 17 (1st December 2019) - Ren, Quanxing; Feng, Dong; Ru, Hongqiang; Jiang, Yan; Ye, Chaochao; Zhang, Yu; Wang, Wei; Zhang, Cuiping
Abstract: A new type of pore structure of B4 C/C preform was fabricated by a resorcinol-formaldehyde (RF) hydrogel gel-casting system. Pore structure controllability of the B4 C/C preform was achieved by adjusting the content of the catalyst Na2 CO3 . Increasing the content of Na2 CO3 could achieve accurate control of the B4 C/C preform from a single macroporous or mesoporous structure to a hierarchical macroporous-mesoporous structure. The reaction bonded boron carbide (RBBC) composites were prepared by the infiltration of B4 C/C preforms of different pore structures with liquid silicon. The residual silicon content and mechanical properties of the RBBC composites were studied. The residual silicon content was controlled by the modification of the open porosity and pore structure of the B4 C/C preforms, and the lowest residual silicon content was 33 vol%. Sample S300, which was prepared through liquid silicon infiltration of a B4 C/C preform with a single mesoporous structure (with the optimum aperture size of 49 nm), had the best mechanical properties, including a flexural strength and fracture toughness of 419 ± 17 MPa and 4.12 ± 0.12 MPa·m 1/2, respectively.